Kecemasan Mahasiswa Fresh Graduate Dalam Melamar Pekerjaan - Anisa Siti Nurjanah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The purpose of this research is to describe the level of anxiety of fresh graduate students applying for jobs. The research focuses on the phonemenon of many fresh graduate students who are unemployed because they feel anxious in applying jobs. Research using library research methods. The data that researchers use in the form of books and journals related to the research topic. The data obtained were analyzed using content analysis techniqus. The results showed that students tend to be more anxious when applying for jobs, especially at the interview stage than if they would be unemployed. Factors that make fresh graduate students feel anxious are the lack of soft skills, lack of information about job and lack of confidence in one’s own abilities.